Fueling the Future: The Case for Heavy-Duty Fuel Cell Electric Vehicles in Sustainable Transportation - Indra Chandra Setiawan; Muji Setiyo (Universitas Muhammadiyah Magelang, 2024)
In the global pursuit of transportation decarbonization, this essay asserts that heavy-duty fuel cell electric vehicle (FCEV) technology represents a more compelling path forward than light-duty FCEVs. The inherent advantages of fuel cells, such as extended range, rapid refueling, and sustained performance, make them well-suited for demanding applications like trucking and public transit. Heavy-duty FCEVs offer significant potential for emissions reduction, integration with existing infrastructure, and economies of scale through commercial fleet adoption. While the upfront investment is substantial, the essay examines how operational benefits can gradually offset costs, emphasizing the importance of heavy-duty FCEVs in sustainable transportation solutions.